Interacting polymer-modification enzymes in heparan sulfate biosynthesis. (1st January 2023) - Zhang, Tianji; Yu, Mingjia; Li, Honglian; Maccarana, Marco; Zhang, Wei; Shi, Deling; Kan, Ying; Zhang, Xiao; Chi, Lianli; Lindahl, Ulf; Li, Hongmei; Li, Jin-ping; et al.
Abstract: Glucuronyl 5-epimerase (Hsepi) converts D-glucuronic acid (GlcA) into L-iduronic acid (IdoA) units, through a mechanism involving reversible abstraction of a proton at C5 of hexuronic acid residues. Incubations of a [4GlcAβ1–4GlcNSO3 α1-]n precursor substrate with recombinant enzymes in a D2 O/H2 O medium enabled an isotope exchange approach to the assessment of functional interactions of Hsepi with hexuronyl 2-O-sulfotransferase (Hs2st) and glucosaminyl 6-O-sulfotransferase (Hs6st), both involved in the final polymer-modification steps. Enzyme complexes were supported by computational modeling and homogeneous time resolved fluorescence. GlcA and IdoA D/H ratios related to product composition revealed kinetic isotope effects that were interpreted in terms of efficiency of the coupled epimerase and sulfotransferase reactions. Evidence for a functional Hsepi/Hs6st complex was provided by selective incorporation of D atoms into GlcA units adjacent to 6-O-sulfated glucosamine residues. The inability to achieve simultaneous 2-O- and 6-O-sulfation in vitro supported topologically separated reactions in the cell. These findings provide novel insight into the roles of enzyme interactions in heparan sulfate biosynthesis. Graphical abstract: Unlabelled Image